The numbers of peripheral regulatory T cells are reduced in patients with psoriatic arthritis and are restored by low-dose interleukin-2 - Jia Wang; Sheng-Xiao Zhang; Yu-Fei Hao; Meng-Ting Qiu; Jing Luo; Yu-Yao Li; Chong Gao; Xiao-Feng Li (SAGE Publishing, 2020)
Background: Although regulatory T cells (Tregs) play crucial roles in the maintenance of immune hemostasis, the numbers of peripheral Tregs in patients with psoriatic arthritis (PsA) remain unclear. We measured these numbers and the efficacy and safety of low-dose interleukin-2 (IL-2) therapy. Methods: We recruited 95 PsA patients, of whom 22 received subcutaneous low-dose IL-2 [0.5 million international units (MIU) per day for 5 days] combined with conventional therapies. The absolute numbers of cells in peripheral CD4 + T cell subsets were measured via modified flow cytometry. Clinical and laboratory indicators were compared before and after treatment. Results: PsA patients had lower peripheral Treg numbers than healthy controls ( p  < 0.01), correlating significantly and negatively with the levels of disease indicators ( p  < 0.05). Although low-dose IL-2 significantly increased the Th17 and Treg numbers in PsA patients compared with the baseline values, the Treg numbers rose much more rapidly than those of Th17 cells, re-balancing the Th17 and Treg proportions. Low-dose IL-2 combination therapy rapidly reduced PsA disease activities as indicated by the DAS28 instrument, thus the number of tender joints, visual analog scale pain, physician global assessment, the dermatology life quality index score, and the health assessment questionnaire score (all p  < 0.05). Conclusion: PsA patients exhibited low Treg numbers. Low-dose IL-2 combination treatment increased these numbers and relieved disease activity without any apparent side effects. Additional studies are required to explore the long-term immunoregulatory utility of IL-2 treatment.